THE CONCEPT OF CREATIVITY IN MODERN PEDAGOGY (Conference Zone, 2022)
Creativity is the knowledge of young students in a certain field and their creativity towards a goal, which directly fulfills the important task of educating creative young people. The development of creative individuals is the guarantee of the country's intellectual wealth, and the formation of divergent thinking of young people through the education of creative individuals is the main issue of today's pedagogy.